FUNGSI POLISI PAMONG PRAJA DALAM PENEGAKAN PERATURAN DAERAH (Studi Penertiban PKL Di Bandar Lampung) - Herni Susiyani (Universitas Lampung, 2016)
Sometimes Civil Service Police acts reactively or repressively without heed to civil rights in doing their operation. Then, Bandar Lampung government has to provide a proper place for street vendors as per local Regulation (The Law Number 8 of 2009). In order to prevent any clashes between civil service police and people in society, especially street vendors, there are several things which need to be done: (1) quality of human resource in civil service police unit need to be improved; (2) Civil Service Police need to use persuasive approach in performing their job; (3) local regulation needs to be aligned; (4) local regulation has to be enforced continuously and appropriately. Keywords: Civil Service Police Function, Local Regulation Enforcement